Pendampingan Penggunaan Media Audio Visual Assisted Text Untuk Meningkatkan Kemampuan Berbicara Pada Siswa Kelas Tambahan Mata Pelajaran Bahasa Inggris Di MA Bidayatul Hidayah Mojogeneng Mojokerto - Risma Rahajeng Lestari; Sherly Citra Putri; Lus Firdaus Zakiya; Ayu Andhika Sugiharta; Vinetta Ashya Sodikin (Universitas Maritim AMNI Semarang, 2023)
Speaking competence in English learning become one of indicator that a learner has mastered the language. The using of proper media to beginner learner is necessary. The purpose of this Community Service is to build motivation and confidence of the English extra class’ students in MA Bidayatul Hidayah. The using of audiovisual assisted text is also followed by integrated activities such as listening, reading, pronouncing, and speaking which is expected that the students can get accustomed to English speech. Then the students’ competence in using English for communication can be improved.